Origami Play Therapy and Preschool Child Development Outcomes: Terapi Bermain Origami dan Hasil Perkembangan Anak Prasekolah - Hikmah, Citra Karima Lailatul; Faridah, Umi; Indanah, Indanah (Indonesian Journal of Innovation Studies, 2026)
General Background: Early childhood represents a critical phase of growth in which optimal stimulation is required to support motor, language, and social development through structured educational and nursing activities. Specific Background: Play-based interventions, including origami activities, are frequently applied in early childhood education settings as routine learning strategies, yet their structured application within nursing-oriented developmental stimulation remains limited. Knowledge Gap: Empirical evidence comparing origami play therapy with routine daily activities using an integrated assessment of fine motor, gross motor, language, and personal–social development is still scarce, particularly in early childhood education institutions. Aims: This study aimed to examine preschool child development following origami play therapy compared with routine daily activities at PAUD (KB–TK) TBS Kajan, Krandon Kudus. Results: Using a quasi-experimental pretest–posttest control group design with 72 preschool children, origami play therapy and routine activities were both associated with significant improvements in developmental outcomes based on Denver Developmental Screening Test assessments, while post-intervention comparisons between groups showed no significant differences. Novelty: The study offers an integrated nursing-based application of origami play therapy assessed across multiple developmental domains within a quasi-experimental framework in an early childhood education context. Implications: These findings support the incorporation of structured origami activities and routine learning practices as complementary approaches in early childhood education and pediatric nursing to support comprehensive preschool development. Highlights• Preschool children showed measurable developmental improvement after structured play-based activities• Origami activities were associated with progress across motor, language, and social domains• Routine daily learning activities also demonstrated comparable developmental gains KeywordsOrigami Play Therapy; Preschool Child Development; Early Childhood Education; Developmental Screening; Pediatric Nursing